NAKIMULI SARAH NATASHA - (:unkn) unknown (My University, 2024)
ABSTRACT The purpose of this study was to examine the extent to which the adoption of electronic procurement systems optimizes the procurement process in local government. Specifically, the study explored the adoption of electronic procurement systems (EPS) in optimizing the procurement process for Mukono District Local Government. The study used a mixed approach research design on a population comprising of stakeholders that is the procurement officers and suppliers in the organization. Data was collected using questionnaires and it was found out effective system utilization rate reduces procurement cycle time through the entire process. In addition to the findings, user adoption rate leads to high levels of stakeholder satisfaction through increased engagement to experience smoother transaction processes, quicker responses and improved access to information. Furthermore, system integration allows electronic procurement systems streamline procurement process by automating workflows and reducing manual tasks hence increasing cost saving rate. The findings indicate that EPS can significantly shorten procurement cycle times, enhance stakeholder satisfaction and increase the rate of cost savings. However, barriers such as inadequate technological infrastructure, insufficient staff training and resistance to change limit the full effectiveness of EPS. The study concludes that a strategic collaborative approach to EPS implementation is essential for improving procurement practices. It offers recommendations for policy-makers and practitioners to facilitate the transition to electronic systems, thereby fostering better governance and service delivery in the public sector. Overall, the research contributes to the existing knowledge on public procurement and serves as a relevant case study for other local governments considering similar advancements.
Adoption of electronic procurement systems in optimizing the procurement process
Undergraduate dissertation